Focal radiotracer uptake in the falciform ligament; A rare lymphoscintigraphic pattern in breast cancer - Amin Saber Tanha; Farid Jafari Zarrin Ghabaei; Pegah Sahafi; Mohammad Ahmadi; Ramin Sadeghi (Asia Oceania Journal of Nuclear Medicine and Biology)
Breast cancer lymphoscintigraphy is a crucial tool in pre-operative assessment, typically revealing sentinel lymph node drainage patterns within axillary and extra-axillary regions. However, rare cases challenge conventional understanding. We report a 67-year-old woman with breast cancer, where lymphoscintigraphy revealed focal uptake within the falciform ligament of the liver, an exceedingly rare phenomenon. Clinical examination and imaging showed no axillary lymph node involvement. Lymphoscintigraphy and subsequent Single-photon emission computed tomography (SPECT)/computed tomography (CT) uncovered two axillary lymph nodes and an atypical focal uptake in the falciform ligament. Histopathology revealed no metastasis in sentinel nodes. The conventional understanding of breast lymphatic drainage primarily involves axillary and extra-axillary pathways, with the falciform ligament rarely implicated. This case suggests a unique lymphatic pathway connecting the breast and liver, possibly influencing metastasis. Factors such as lymphatic obstruction and valvular incompetency may contribute. This case highlights the importance of comprehensive lymphatic mapping in breast cancer evaluation and underscores the need for further research into atypical lymphatic pathways.